Dual-use biology: building trust and managing perceptions of intent. Issue 4 (1st September 2020) - Lentzos, Filippa
ABSTRACT: At a time of heightened concern about potential future biological-weapons threats, this article considers how the international community can use the Biological and Toxin Weapons Convention framework to strengthen compliance monitoring of rapidly increasing dual-use capacities around the globe. It presents three conceptual layers within the treaty regime which states can draw from to inform their compliance judgments: one legally binding, one politically binding, and one wholly voluntary. The article outlines how these were established and how they have been used so far, and argues for an incremental, inclusive, practical, and forward-looking approach to evolving these structures to better manage perceptions of the intent behind dual-use capacities, and to further trust between states.